An Organodiselenide Comediator to Facilitate Sulfur Redox Kinetics in Lithium–Sulfur Batteries - Zhao, Meng; Chen, Xiang; Li, Xi‐Yao; Li, Bo‐Quan; Huang, Jia‐Qi (Advanced materials (Weinheim), 2021)
Lithium–sulfur (Li–S) batteries are considered as promising next‐generation energy storage devices due to their ultrahigh theoretical energy density, where soluble lithium polysulfides are crucial in the Li–S electrochemistry as intrinsic redox mediators. However, the poor mediation capability of the intrinsic polysulfide mediators leads to sluggish redox kinetics, further rendering limited rate performances, low discharge capacity, and rapid capacity decay. Here, an organodiselenide, diphenyl diselenide (DPDSe), is proposed to accelerate the sulfur redox kinetics as a redox comediator. DPDSe spontaneously reacts with lithium polysulfides to generate lithium phenylseleno polysulfides (LiPhSePSs) with improved redox mediation capability. The as‐generated LiPhSePSs afford faster sulfur redox kinetics and increase the deposition dimension of lithium sulfide. Consequently, the DPDSe comediator endows Li–S batteries with superb rate performance of 817 mAh g−1 at 2 C and remarkable cycling stability with limited anode excess. Moreover, Li–S pouch cells with the DPDSe comediator achieve an actual initial energy density of 301 Wh kg−1 and 30 stable cycles. This work demonstrates a novel redox comediation strategy with an effective organodiselenide comediator to facilitate the sulfur redox kinetics under pouch cell conditions and inspires further exploration in mediating Li–S kinetics for practical high‐energy‐density batteries. An organodiselenide, diphenyl diselenide (DPDSe), is proposed to accelerate the sulfur redox kinetics as a redox comediator, which endows Li–S batteries with superb rate performance, remarkable cycling stability, and high actual energy density of 301 Wh kg−1. This work demonstrates a novel redox comediation strategy to facilitate the sulfur redox kinetics under practical pouch cell conditions.